FRI0032 Tophus formation limits neutrophil-induced inflammation. (23rd January 2014) - Schorn, C.; Zhao, Y.; Janko, C.; Schett, G.; Herrmann, M.
Abstract : Background: In the presence of sodium uric acid precipitates as monosodium urate (MSU) 1 . In kidney and joints MSU induces renal calculi and gouty arthritis, respectively. The latter is characterized by red, hot and swollen arthritic joints and can be used as a model for neutrophil-mediated inflammation. After migration into the joint space and the synovial membrane neutrophil ingest MSU crystals and secret chemotactic mediators, intensifying the inflammation 2 . Objectives: In our assays we compared the effect of monosodium urate crystals (MSU) on low density cell cultures, typical for the initial phase of tissue infiltration, with high density cell cultures, a hallmark for the late phase of tissue infiltration. Methods: Human PMN (polymorphonuclear cells) were incubated with MSU crystals and analysed by fluorescence microscopy (DAPI). For measurements of reactive oxygen species (ROS) anticoagulated human blood was incubated with 10 μM DCFH-DA. After erythrocyte lysis the intracellular DCF-fluorescence of the leukocytes was recorded by flow cytometry. The cytokine production in culture supernatants of low density cell cultures (1-5 Mio/ml) and high density cell cultures (100 Mio/ml) was analysed by multiplex bead technology and quantified by cytofluorometry. Moreover, tophi were generated in vitro by incubation of high density cell culture of PMN with MSU for 30 minutes at 37°C. In addition, mice were treated intraperitoneally with MSU crystals resulting in generation of gouty tophi. Paraffin sections of murine and human tophi were analysed by nuclear staining and immunohistology. Results: In the in vitro low density cell cultures (5 Mio/ml) we observed the ROS-dependent NETting of neutrophils induced by MSU crystals with massive cytokine and chemokine release. In contrast, in high density cell cultures (100 Mio/ml) and after in vivo injection of MSU into the peritoneum of mice gouty tophi are formed. The formation of the tophus in vitro is inhibited by DNase- 1 and EDTA treatment. Interleukin (IL)-8 and IL-1RA are released by the tophi whereas other cytokines and chemokines, exogenously added to the medium, are sequestered and degraded by the tophus. The disappearance of cytokines and chemokines is inhibited by PMSF, a serine protease inhibitor, and reduced by proteinase 3 inhibitors. Conclusions: We conclude that individual NETting neutrophils act as pro-inflammatory stimulus by massive cytokine release, whereas tophi formed in areas of massive NETting are cytokine sinks that contribute to the resolution of inflammation by proteases. References: Schorn, C., et al. Sodium overload and water influx activate the NALP3 inflammasome. J Biol Chem 286, 35-41 (2011) Ryckman, C., et al. Monosodium urate monohydrate crystals induce the release of the proinflammatory protein S100A8/A9 from neutrophils. J Leukoc Biol 76, 433-440 (2004). Disclosure of Interest: None Declared